The role of science, technology and innovation in economic growth: a theoretical and empirical review and its implications for Vietnam - Lien, Nguyen Thuy; Trung, Hoang Van; Minh, Dinh Tuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The paper conducts theoretical and empirical review on the role of science, technology and innovation (STI) in economic growth. In general, economic growth theories and practical experience around the world all show that STI has long-term effects on economic growth. However, the latter economic growth theories show that, depending on particular national innovation systems, the impact of STI on economic growth differs from country to country. Practical experience from successful countries shows that, in order to sustain long-term economic growth, each country needs to build a national innovation system tailored to its conditions and circumstances, where the private sector should play a central role. The system must ensure to generate a workforce of high quality and consistent with the needs of the market. Code: 20122901